PENGARUH CITRA MEREK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN FRIED CHICKEN D’KRIUK TEROGONG CILANDAK BARAT - Simatupang, lucy63; Putra, Satria Dwi (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
ABSTRACT This exploration was controlled on Fried Chicken D’Kriuk Terogong West Cilandak consumer. The spirit of this study was to decide the performance of brand image, price and location on buy compromise of Fried Chicken D’Kriuk Terogong Cilandak Barat. The sample used within this study make to 100 a respondents. This type of exploration is a casual test an whichever appoint the relationship or control between one or even other independent variables on the dependent variable. The exploration method use collaborative linear regression analysis beside the help of data processing using SPSS software version 26. The results of this study signify that brand image and price to have a significant reaction on purchase decision, while location has no significant reaction on purchase decision.